Legitimasi Hukuman Mati bagi Koruptor dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Muhammad Fariz Ash Shiddiq Ibrahim Mamesah; Irfan Azkabillah Al-Musthofa; Lintang Nuraini; Urpha Rekyaningrum; Najwa Bilqis Khoiruna; Shinta Adilla; Shinta Nabila (Eshraq: Journal of Islamic Studies, 2025)
Corruption remains a critical issue in Indonesia and is widely categorized as an extraordinary crime due to its extensive social, moral, and economic impact. This study examines the debate on the application of the death penalty for corruption by comparing Islamic law and Indonesia’s positive legal system. In Islamic law, scholars present diverse views. Some, such as Wahbah az-Zuhaili and Imam Muhib al-Thabari, allow capital punishment when corruption causes widespread harm and threatens public stability, based on the principle of preventing greater harm. Other scholars classify corruption under ta’zir, meaning that punishment is flexible and determined by the authority according to the level of damage caused. Meanwhile, Indonesia’s legal framework, through Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, provides space for the death penalty under specific conditions, although no court has ever enforced it. The study concludes that both legal systems acknowledge the severity of corruption, but the death penalty should only be considered in exceptional circumstances with strict regard to justice, public welfare, and human rights.